Artificial Intelligence and the Issue of Information Protection: Legal Aspect - Kudryavtsev, Vladislav; Leontev, Mikhail; Riabchenko, Aleksandr; Akhyadov, Elman; Panova, Nataliia; Sinyukov, Vasily (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
The development and use of artificial intelligence (AI) brings new challenges related to information protection, which is an important concern in the legal context of today's digital era. This article aims to analyse the legal aspects of information protection in the development and application of AI. This research was conducted using qualitative methods through a literature approach and analysis of legislation, both at the national (Russian) and international levels. The analysis results show that the main objects of information protection in the context of AI include trade secrets, professional secrets, and personal data. Therefore, entities holding trade and professional secrets and processing personal data must handle this issue under the applicable legal framework. This article concludes that existing regulations must evolve to accommodate information protection challenges in the dynamic AI ecosystem.